The big book of makerspace projects : inspiring makers to experiment, create, and learn - Graves, Colleen, ....-; Graves, Aaron, ....- (New York : McGraw-Hill, 2017)
This easy-to-follow guide features dozens of DIY, low-cost projects that will arm you with the skills necessary to dream up and build your own creations. The Big Book of Makerspace Projects: Inspiring Makers to Experiment, Create, and Learn offers practical tips for beginners and open-ended challenges for advanced makers. Each project features non-technical, step-by-step instructions with photos and illustrations to ensure success and expand your imagination. You will learn recyclables hacks, smartphone tweaks, paper circuits, e-textiles, musical instruments, coding and programming, 3-D printing, and much, much more!